Nutrition and feeding of organic poultry - Blair, Robert, 1933- (CABI, 2008)
This book presents advice and guidelines on how appropriate diets can be formulated and how feeding programmes can be integrated into an organic poultry production system. The topics include the aims and principles of organic poultry production, elements of poultry nutrition, approved ingredients for organic diets, diets for organic poultry production, choosing the right poultry breed and strain, integrating feeding programmes into organic production systems and conclusions and recommendations for the future of organic poultry egg and meat production and feeding. This book will be of interest to nutritionists and organic producers in formulating diets and feeding programmes for organic poultry production, and for regulatory authorities in several countries addressing nutritional issues relevant to future revisions of the regulations from an animal nutrition perspective.